Myo-inositol versus metformin pre-treatment and the follicular-fluid metabolome in PCOS women undergoing IVF: a double-blind randomized trial - Syaifudin; Dessy Agustina; Sarah Istiqomah (Phlox Institute: Indonesian Medical Research Organization, 2026)
Background: Polycystic ovary syndrome (PCOS) impairs oocyte quality and complicates in vitro fertilization (IVF). Metformin and myo-inositol are widely prescribed insulin sensitizers, yet their comparative effects on the human follicular-fluid (FF) metabolome and IVF outcomes have rarely been examined head-to-head. Objective: To compare myo-inositol and metformin pre-treatment in terms of the FF metabolome and embryologic, clinical, and safety outcomes in women with PCOS undergoing IVF. Methods: In a double-blind, block-randomized (1:1) trial at two tertiary IVF centers in Jakarta and Palembang, Indonesia, 150 women with PCOS (Rotterdam criteria; aged 20–35 years; BMI 18.5–29.9 kg/m²) received myo-inositol 4 g/day (n=75) or metformin 1500 mg/day (n=75) for 12 weeks before and during a GnRH-antagonist protocol. FF was analyzed by LC-MS/MS. Analyses were intention-to-treat and included multivariable logistic regression, ROC analysis, and number needed to treat (NNT). Results: Myo-inositol yielded more MII oocytes (11.6 ± 3.4 vs 10.1 ± 3.6; p=0.010), higher fertilization (72.5% vs 66.8%; p=0.006), and more top-quality embryos (4.3 ± 1.8 vs 3.4 ± 1.7; p=0.002). Clinical pregnancy was 48.0% versus 33.3% (unadjusted p=0.069; adjusted OR 2.18, 95% CI 1.04–4.57; p=0.039; NNT 7). Moderate–severe OHSS (6.7% vs 18.7%; p=0.038; NNT 8) and gastrointestinal events (9.3% vs 34.7%; p<0.001; NNT 4) were lower with myo-inositol. FF myo-inositol, D-chiro-inositol, and antioxidant capacity were higher; FF myo-inositol predicted pregnancy (AUC 0.78). Conclusion: Myo-inositol pre-treatment shifted the FF metabolome toward a pro-developmental antioxidant profile and improved embryologic outcomes and tolerability versus metformin. The clinical-pregnancy signal remains provisional because the trial was underpowered for this endpoint and the unadjusted comparison was not significant; adequately powered live-birth trials are needed.